ANALYSIS OF MITOCHONDRIAL DNA SEQUENCES USING NEXT-GENERATION SEQUENCING TECHNOLOGY FOR HUMAN IDENTIFICATION: OPPORTUNITIES AND CHALLENGES - Swati Arora1, Dr. Ajay Kumar2, Dr. Rajeev Kumar3 (Chelonian Research Foundation, 2023)
Next-generation sequencing (NGS) technology has revolutionized the field of forensic science and has brought about significant improvements in human identification. Among the various applications of NGS in forensic science, mitochondrial DNA (mtDNA) analysis has received considerable attention due to its high abundance, easy accessibility, and maternal inheritance pattern. Mitochondrial macro-haplogroup M predominated (58%). Due to their distinct coalescent histories, we projected different expansion times for North, East, and West Indians. Due to frequent free-mixing and rapid Indo-European language transmission, these populations are admixed and lack a subpopulation structure. Due to endogamy, South Indians had a much older expansion time (28kya) and slight genetic variation. We've found five West Indians (16069, 16169, 16206, 215 & 243), four North Indians (16170, 16181, 16185 & 285), three East Indians (16224, 16344 & 41), and one South Indian (480) hotspot spots for human identification. A larger cohort and numerous molecular markers must validate this pilot-scale study's findings. Keywords: Next-generation sequencing (NGS), mitochondrial DNA (mtDNA), human identification, forensic science.